ACCOUNTING FUNDAMENTALS AND VARIATIONS OF STOCK PRICE: FORWARD LOOKING INFORMATION INDUCEMENT - Sumiyana, Sumiyana (Journal of Indonesian Economy and Business, 2011)
This study investigates a permanent issue about low association between accountingÂ fundamentals and variations of stock prices. It induces not only historical accountingfundamentals, but also forward looking information. Investors consider forward lookingÂ information that enables them to predict potential future cash flow, increase predictiveÂ power, lessen mispricing error, increase information content and drives future priceÂ equilibrium. The accounting fundamentals are earnings yield, book value, profitability,Â growth opportunities and discount rate or they could be called as five-related-cash flowÂ factors. The forward looking information are expected earnings and expected growthÂ opportunities. This study suggests that model inducing forward looking information couldÂ improve association degree between accounting fundamentals and the movements of stockÂ prices. In other words, they have higher value relevance than not by inducing. Finally, thisstudy concludes that inducing forward looking information could predict stock priceÂ accurately and reduce stock price deviations from their fundamental value. It also impliesthat trading strategies should realize to firmâs future rational expectations.Keywords: earnings yield, book value, profitability, growth opportunities, discount rate,Â accounting fundamentals, forward looking, value relevance